The Toyota Engagement Equation : How to Understand and Implement Continuous Improvement Thinking in Any Organization - Richardson, Tracey M.; Richardson, Ernie (McGraw-Hill Education, 2017)
The formula for Lean success! Toyota veterans reveal how to build continuous improvement into your company?s DNA. Ever since Toyota introduced the revolutionary Toyota Production System (TPS), businesses have tried to replicate Toyota?s success. Few have succeeded over the long term. What businesses have failed to realize is that TPS calls for a fundamentally different way of thinking.Now, at long last, here is a straightforward guide that make sense of the thinking culture behind Toyota?s phenomenal success. In its pages, authors Tracey and Ernie Richardson speak from the heart as Toyota employees who worked in the Kentucky factory when the company was first introducing its people-first approach in the U.S., and went on in the ensuing decades to teach Lean thinking around the world.The Toyota Engagement Equation, the authors take you through Toyota?s own journey of discovery. This deep dive into the company?s game-changing work practices reveals how employees were developed, how they were taught to spot and define problems through standardization, how they were coached to solve them, and how they were encouraged to improve their thinking as they moved forward.And you?ll see how Toyota developed this simple but profoundly effective approach into an overall management system?and how you can achieve amazing results in your company through the same system.In the world of Lean design and implementation handbooks, The Toyota Engagement Equation stands out as a fresh, unique, and authoritative guide to building your business into the Toyota of your industry. As the authors see it, TPS has now evolved to the ?Thinking People System!?.